2020
DOI: 10.5194/hess-2020-303
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving Soil Moisture Prediction of a High–Resolution Land Surface Model by Parameterising Pedotransfer Functions through Assimilation of SMAP Satellite Data

Abstract: Abstract. Pedotransfer functions are used to relate gridded databases of soil texture information to the soil hydraulic and thermal parameters of land surface models. The parameters within these pedotransfer functions are uncertain and calibrated through analyses of point soil samples. How these calibrations relate to the soil parameters at the spatial scale of modern land surface models is unclear, because gridded databases of soil texture represent an area average. We present a novel approach for calibrating… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Even though model performance is not the same as achieved with calibrated conceptual or empirical models, it allows us to determine the effects of vegetation changes on the hydrological cycle. JULES' ability to faithfully represent hydrological land-surface processes in Great Britain has been evaluated in several studies 58,79,80 and the plant functional type parameters it uses at global scales 81,82 . To validate the ability of our configuration of JULES to represent soil moisture and potential evapotranspiration rates, we compare the model output with observations from twelve COSMOS-UK sites within our catchments covering grasslands, croplands, coniferous and broadleaf woodland 83 (Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Even though model performance is not the same as achieved with calibrated conceptual or empirical models, it allows us to determine the effects of vegetation changes on the hydrological cycle. JULES' ability to faithfully represent hydrological land-surface processes in Great Britain has been evaluated in several studies 58,79,80 and the plant functional type parameters it uses at global scales 81,82 . To validate the ability of our configuration of JULES to represent soil moisture and potential evapotranspiration rates, we compare the model output with observations from twelve COSMOS-UK sites within our catchments covering grasslands, croplands, coniferous and broadleaf woodland 83 (Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…A number of these enhancements are being currently delivered and coordinated through the Hydro-JULES programme (https://hydrojules.org/). Hydro-JULES research is also deriving improved land surface parameters through a data assimilation framework using the COSMOS observations (Cooper et al, 2020;Pinnington et al, 2020).…”
Section: Recommendations For Model Development and Evaluationmentioning
confidence: 99%
“…The depth of AWRA-L upper layer is different from the general depth of the surface SM (5-cm). Pinnington et al (2021) found the assimilation results of LSM are usually consistent while running with either a 10-cm top layer or a 5-cm top layer. The comparison between AWRA-L upper layer and other independent surface SM can be considered fair.…”
Section: Awra-l Soil Moisture Analysismentioning
confidence: 82%